2020
DOI: 10.1111/aos.14330
|View full text |Cite
|
Sign up to set email alerts
|

Association of sex with the global burden of glaucoma: an analysis from the global burden of disease study 2017

Abstract: To investigate the association of sex with the global burden of glaucoma by year, age and socio-economic status using disability-adjusted life years (DALYs). Method: The global, regional and national sex-specific DALY numbers, crude DALY rates and age-standardized DALY rates caused by glaucoma, by year and age, were obtained from the Global Burden of Disease Study 2017. Human development index (HDI) in 2017 as a national socio-economic indicator was obtained from the Human Development Report. t-Test and linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…This may be due to the longer life expectancy of females. Males had higher DALYs rate of glaucoma than females which is consistent with the global analysis by Zhang 11 and Ye 17 but inconsistent with the analysis by Wang. 10 Above all, the rapidly increasing DALYs rate as shown in Figure 3 necessitates the development of new methods for glaucoma screening and diagnosis.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…This may be due to the longer life expectancy of females. Males had higher DALYs rate of glaucoma than females which is consistent with the global analysis by Zhang 11 and Ye 17 but inconsistent with the analysis by Wang. 10 Above all, the rapidly increasing DALYs rate as shown in Figure 3 necessitates the development of new methods for glaucoma screening and diagnosis.…”
Section: Discussionmentioning
confidence: 43%
“…18 On the contrary, Ye revealed that the age-standardized DALY rates decreased consistently from 10.7 in 1990 to 9.4 in 2017 among men and from 8.8 in 1990 to 8.0 in 2017 among women. 17 We give several potential reasons for the variation. First, the strategies for the prevention and control of glaucoma were different among regions.…”
Section: Discussionmentioning
confidence: 99%
“…A larger epidemiological and genetic study in individuals of different ancestries will clarify the role of GWAS signals identified here or other additional signals in differential risk burden between ancestries and genders, distinct from what has been reported globally. 153 We further performed extensive in-silico validation of the SIX6 and CDKN2B-AS1 loci, using GTEx and EHR data across BioVU and UKBB. In our study we found evidence of significant interaction between SIX6 rs33912345 and causal variants in chr9p21.3, with concomitant effect on expression of a primary cilia gene CDKN2A, and CDKN2B in the CDKN2B-AS1 locus.…”
Section: Discussionmentioning
confidence: 99%
“…A larger epidemiological and genetic study in individuals of different ancestries will clarify the role of GWAS signals identified here or other additional signals in differential risk burden between ancestries and genders, distinct from what has been reported globally. 103…”
Section: Discussionmentioning
confidence: 99%
“…Females are known to have higher rates of blindness globally 38 even when controlling for socioeconomic status 39 . Unequal access to eye care services according to socioeconomic status (such as income and education levels) and by socio-cultural status (for example by gender) was considered a factor for visually impaired people, particularly in low income countries 38,40 . At the same time, gender difference associated with visual impairment and health status remains controversial 41,42 .…”
Section: Discussionmentioning
confidence: 99%